Action Research Training: Its Effect on the Research Attitude, Knowledge, and Performance of Teachers - Fajardo, Edna Gando; Digo, Gerry Sanez (FKIP Universitas Lampung, 2023)
Action Research Training: Its Effect on the Research Attitude, Knowledge, and Performance of Teachers. Objectives: This study aimed to determine the effect of action research training on the attitude, knowledge, and performance of teachers in research. Methods: This study used the mixed methods sequential explanatory design. Findings: Action research training that involved collaboration, coaching, and research support from mentors did not significantly improve the attitude and knowledge in research, but was effective in enhancing the performance of teachers in action research proposal preparation. Moreover, the participants claimed that the action research training was useful, effective, and transformative. Conclusions: Training, collaboration, support from mentors, favorable attitude, and knowledge contributed to the increased performance of teachers in action research. Keywords: attitude in research, knowledge in research, performance in research, teacher-researchers, action research training.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202314